Studi Tematik Hadis Tentang Mahar dan Budak dalam Tinjauan Syar’i - Shohibul Umam; Hafidz Taqiyuddin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Dowry and slaves are two different things. Mahar is property or something given by a husband to his wife as part of their marriage. This is supported by a hadith from Muhammad Shallallahu 'Alaihi wa Sallam which says